1980
DOI: 10.1071/ar9800821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of level of larval intake on the productivity and physiological and metabolic responses of lambs infected with Trichostrongylus colubriformis

Abstract: The interrelationships between level of exposure to Trichostrongylus colubriforn~i.s infection, production loss, and the physiological and metabolic changes associated with the development of the disease were studied over 24 weeks in groups of weaner lambs on larval dosing regimes (LDR) of either 0, 300, 950, 3000, 9500 or 30,000 infective larvae per week. During the first 12 weeks faecal egg counts generally accorded with the level of larval dosing, but thereafter declined, and at 24 weeks worm counts showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 3 publications
5
49
1
1
Order By: Relevance
“…Parasitic infection has increased the rates of synthesis of hepatic constitutive proteins Bermingham et al 2006). The 4% decrease (P < 0.15) in skin FSR I observed in the current study is consistent with previous studies in parasitized sheep (Symons and Jones 1975;Steel et al 1980Steel et al , 1982. Whilst these studies have shown decreased skeletal muscle protein synthesis during parasitic infection, similar infection protocols to the current study showed that an adult T. colubriformis infection did not affect the FSR of the biceps femoris (Bermingham et al 2006).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Parasitic infection has increased the rates of synthesis of hepatic constitutive proteins Bermingham et al 2006). The 4% decrease (P < 0.15) in skin FSR I observed in the current study is consistent with previous studies in parasitized sheep (Symons and Jones 1975;Steel et al 1980Steel et al , 1982. Whilst these studies have shown decreased skeletal muscle protein synthesis during parasitic infection, similar infection protocols to the current study showed that an adult T. colubriformis infection did not affect the FSR of the biceps femoris (Bermingham et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…This point was covered in detail in Bermingham et al (2006). Briefly, the majority of the studies in sheep reported in the literature have involved long-term constant (at least weekly) infection procedures (e.g., Steel et al 1980;Jones and Symons 1982;Yu et al 2000) and/or larger infection dose (Steel et al 1980;Jones and Symons 1982). It is also possible that alterations in whole-body and tissue protein synthesis would have been observed at an earlier stage of parasite establishment, such as when the lamb was first infected with T. colubriformis and when faecal egg production was at its highest point during the infection (around 26 d post-infection).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without pairfed controls it is difficult to separate and quantify the precise importance of the two components of reduced feed intake and increased nutrient costs for overall efficiency. The calculation of the effect of infection on both VFI and nutrient utilization is heavily dependent on the duration and extent of the pathophysiology of infection, which several studies have shown is greatest during the period immediately preceding the host's ability to limit FEC (Steel et al, 1980;Kimambo et al, 1988). The benefit of the higher protein diet in the present work appears to have been in either permitting or accelerating the development of an effective immune response as H-IF sheep were able to regulate FEC by day 70 while there was no evidence for such ability in L-IF sheep.…”
Section: Discussionmentioning
confidence: 99%
“…mucus, plasma leakage or sloughed cells; Kimambo et al, 1988) and/or as N excretion in urine and faeces (Sykes and Coop, 1976). These effects may, in part, explain the decreased growth performance (Sykes and Coop, 1976;van Houtert et al, 1995) and production (Steel et al, 1980 and that is observed during parasite infections in lambs.…”
Section: Introductionmentioning
confidence: 99%